2020
DOI: 10.18100/ijamec.803400
|View full text |Cite
|
Sign up to set email alerts
|

Follicle Detection for Polycystic Ovary Syndrome by using Image Processing Methods

Abstract: Polycystic ovary syndrome is a hormonal disorder seen in many women. It occurs by the combination of many small and benign cysts in the ovaries. These cysts, called follicles, create a special pattern in the ovaries observed with ultrasound imaging. The number, structure, and size of these follicles provide important information for the diagnosis of ovarian diseases. In this study, two different methods of follicle detection are tested for Polycystic Ovary Syndrome. The first method consists of noise filtering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In this way, unimportant details were removed, and important regions were highlighted. In this study, two different methods were used for the pre-processing stage [25].…”
Section: Follicle Detectionmentioning
confidence: 99%
“…In this way, unimportant details were removed, and important regions were highlighted. In this study, two different methods were used for the pre-processing stage [25].…”
Section: Follicle Detectionmentioning
confidence: 99%
“…For example, Mandal et al 15 suggested a technique to diagnose PCOS by automatically segmenting cysts and follicle regions from ultrasound images; for which they employed multiple digital image processing steps such as histogram equalization, K-means clustering, median filtering, and morphological erosion on 19 ultrasound pictures. Yilmaz et al 16 tested and compared two methods of follicle detection using image processing techniques to diagnose PCOS; where the first approach includes noise reduction (Median, Average, Gaussian, and Wiener Filters), contrast modification (histogram equalization and adaptive thresholding), binarization, and morphological procedures. ; and the second approach comprises of noise reduction (Gaussian Filter and Wavelet Transform), k-means clustering, hole filling and morphological operations.…”
Section: Related Workmentioning
confidence: 99%
“…In ultrasound device, two-dimensional ovary images in grey and white/black colour are generated. The generated polycystic ovarian and normal ultrasound images have been different from one another [13,14]. Normally, the patients affected by PCOS consist of 10-12 cysts present in the ovary, but more than 10 cysts are more enough to diagnose the disorder from the ultrasound images.…”
Section: Srinivas Publicationmentioning
confidence: 99%